2010
DOI: 10.1021/jp104753t
|View full text |Cite
|
Sign up to set email alerts
|

Constant-pH Molecular Dynamics Simulations Reveal a β-Rich Form of the Human Prion Protein

Abstract: The misfolding of the prion protein (PrP) into a pathogenic β-rich form (PrP(Sc)) has been suggested to occur in the endocytic pathway, triggered by low pH. In this work we performed several constant-pH molecular dynamics simulations of human PrP 90-231 in the pH range 2-7, totaling more than 2 μs. We observed a strong conformational pH dependence where on average the helix content decreased and the β content increased toward acidic pH. Unlike some proposed models, the flexible N-terminus region did not gain s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
96
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(105 citation statements)
references
References 76 publications
(196 reference statements)
9
96
0
Order By: Relevance
“…114 Several computational studies have showed increased structural dynamics in the α1 region during the early stages of PrP misfolding. 115,116 Page 10 of 44 Biochemistry 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 11 The loop between β2 and α2 is another region that has been suggested to be critical for the misfolding of PrP. 117 The conformation and rigidity of this loop appears to determine prion disease transmission and susceptibility of a species.…”
Section: Structural Similarity Between Amyloid Fibrils and Soluble Olmentioning
confidence: 99%
See 1 more Smart Citation
“…114 Several computational studies have showed increased structural dynamics in the α1 region during the early stages of PrP misfolding. 115,116 Page 10 of 44 Biochemistry 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 11 The loop between β2 and α2 is another region that has been suggested to be critical for the misfolding of PrP. 117 The conformation and rigidity of this loop appears to determine prion disease transmission and susceptibility of a species.…”
Section: Structural Similarity Between Amyloid Fibrils and Soluble Olmentioning
confidence: 99%
“…72,123-125 Indeed, several studies point out that this region could act as a nucleation site for PrP misfolding, and hence, the initial conformational changes could begin in this region. 115,126,127 Interestingly, the C-terminal stretch of α2 (sequence stretch TVTTTT) is very unusual in its sequence composition.…”
Section: Acs Paragon Plus Environmentmentioning
confidence: 99%
“…Apart from studying the native dynamics of recPrP in solution, MD simulation has also been used to sample possible early events in prion protein misfolding, either by simulating under conditions that are known to promote misfolding, such as low pH [56,57,[59][60][61], or by using enhanced, non-physical sampling methods [62,63]. As details of the misfolding pathway are unknown and difficult to probe by experiment, the results obtained can only suggest potential events and conformations along the pathway.…”
Section: The Dynamics and Misfolding Of The Wild-type Prion Proteinmentioning
confidence: 99%
“…The results obtained for their studies in a diversity of biomolecular systems reveal the vast possibilities of the method. Examples include investigation on the pH-dependent conformational states of the analgesic dipeptide kyotorphin (L-Tyr-L-Arg) (Machuqueiro and Baptista 2007), the possibility of a trigged pH action on the misfolding of the prion protein into a pathogenic β-rich form (Campos et al 2010), the pH effects on the reversibility of prion misfolding (Vila-Viçosa et al 2012), a pH titration of all constituent lipids of a 25% DMPA/DMPC bilayer membrane model (Santos et al 2015), and the tight coupling between protonation and conformation for cytochrome c oxidase (Oliveira et al 2016).…”
Section: Other Common Constant Ph Simulation Methodsmentioning
confidence: 99%